Thermal therapy and delayed onset muscle soreness - Hassan, E. S. A. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: In this study the application of cold water (CW) or warm water (WW) for the recovery delayed onset muscle soreness (DOMS) was investigated in comparison with a control group without the application of water (CO) after eccentric exercise. METHODS: The main study took place in a randomized, controlled study design on 60 healthy, moderately athletic young men (aged 22 years), classified into 3 groups with 20 men per group. The load was equivalent to the 70% of 1 RM, one-repetition maximum at the Deadlift (Bent Leg). Exercise consisted of 10 sets of 10 eccentric contractions of the Hamstrings muscle group after which they were exposed to either CW (20 °C), or WW (38 °C) or no intervention at all (CO). Blood samples were taken 30min before, after and 1, 2 and 6 hours after performing the exercise. RESULTS: The exercise showed to a clear increase in the muscle stress parameters without significant difference in results between the groups. The application of WW after exercise resulted in a prominent decrease in muscle cell reaction. In addition, a significant decrease was noticed in the skeletal troponin I (sTnI), creatin kinase (CK) and myoglobin (Mb) after ww. CONCLUSION: These results are indicative that the exposure of CW (20 °C/30 min) after exercise would lead to an elevated muscle cells stress reaction. On the other hand exposure to WW (38 °C/30 min) leads to a decrease in the exercise-induced deflection of muscle cell reaction.